The inspection of 1774 of the St. Mary de la Vega’s College of the University of Salamanca - Astorgano Abajo, Antonio (CIAN-Revista de Historia de las Universidades, 2013)
The St. Mary de la Vega’s College of the University of Salamanca is one more of the great quantity of colleges that were founded under protection of Salamanca Study. St. Mary de la Vega’s College have been neglected by most researches. After a brief introductory history of the institution, this article goes in detail into his story in the 18th century. This work makes an analysis about the inspection of 1774, and his matter sas important as its performance and the last constitutions during the 18th century.
Keywords: College of La Vega; University Schools of Salamanca; Basilica of San Isidoro; Gaspar González Candamo; Meléndez Valdés